STUDENTS’ COMPREHENSIONIN UNDERSTANDING ENGINEERING ENGLISH THROUGH READING INSTRUCTION - Utomo, Addy (Jurnal Industri Inovatif, 2013)
Englishis an important language to communicate for any levels of students. Unfortunetely, although the students get this language from early, they still cannot master it well. They are not good in passing many skills of English, just like the speakingskill, writingskill, readingskill, and also listening skill. As a matter of the fact above, it makes the teachers have an additional duty to give a better method in teaching them in order that they can accept the lesson well and get a better result at the end. That is why the researcher is interested in conducting a method, reading instruction, to be implemented in EngineeringDepartment of ITN Malang in the first semester.Here, the researcher faces a problem, thatis “how can reading instructionincrease students’ comprehension inunderstanding EnglishEngineering”. This study is intended to see how the reading instructioncan increase students’ comprehension in understanding English Engineering. The researcher uses two types of reading instruction, those are: direct and indirect instruction.Getting the data, the researcher uses a class action research because he takes the data by himself. He teaches the students by the help of a collaborator. Toget the data, the researcher uses an interview, observation, test, questionnaire, and also documentation as the instruments. Here, the researcher conducts two cycles, in which every cycle consists of four steps, those are: planning, acting, observing and evaluating, and also reflecting. During the two cycles conducted, the students get improvement. At the first cycle, the students get a mean as 77.75. Meanwhile at the second cycle, they get the mean as 88.67. From this result, it is shown that the method is successful. Some suggestions are extended for theother researchers. The other researchers are suggested to apply this method to other skill of English, just like at speaking subject or take the different subject of the study for the next research.